Electrochemical behaviour of Ni and Ni-PVC electrodes for the electroxidation of ethanol (Tingkah Laku Elektrokimia Pengoksidaan Etanol Menggunakan Elektrod Ni dan Ni-PVC) - Mohd Syafiq Hamdan,; Norazzizi Nordin,; Siti Fathrita Mohd Amir,; Riyanto,; Mohamed Rozali Othman, (Universiti Kebangsaan Malaysia, 2011)
In this study, two nickel based electrodes were prepared; nickel foil and nickel-polyvinylchloride (Ni-PVC), in order to study their electrochemical behavior using cyclic voltammetry, CV and chronocoulometry, CC. Ni electrode was prepared from Ni metal foil while Ni-PVC electrode was prepared by mixing a weighed portion of Ni powder and PVC in THF solvent, swirled until the suspension was homogeneous and drying the suspension in an oven at 50oC for 3 h. The dry sample was then placed in a 1 cm diameter stainless steel mould and pressed at 10 ton/cm2. From CV data, Ni-PVC electrode showed a better electrochemical behavior compared to Ni metal foil electrode. The use of Ni-PVC electrode at higher concentration of supporting electrolyte (1.0 M KOH) was better than at lower concentration of the same supporting electrolyte in electroxidation of ethanol. In addition to acetic acid, the oxidation of ethanol also produced ethyl acetate and acetaldehyde.